2016
DOI: 10.5194/angeo-34-143-2016
|View full text |Cite
|
Sign up to set email alerts
|

A method to improve the utilization of GNSS observation for water vapor tomography

Abstract: Abstract. Existing water vapor tomographic methods useGlobal Navigation Satellite System (GNSS) signals penetrating the entire research area while they do not consider signals passing through its sides. This leads to the decreasing use of observed satellite signals and allows for no signals crossing from the bottom or edge areas especially for those voxels in research areas of interest. Consequently, the accuracy of the tomographic results for the bottom of a research area, and the overall reconstructed accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Over the past decade, numerous studies demonstrated the potential of GNSS tomography to retrieve 4-D humidity fields. Unfortunately, because the quality of the reconstructed profiles is limited by the constellation of GNSS satellites, the geographic distribution of ground-based receivers, and observation errors (Chen and Liu, 2014;Rohm et al, 2014;Shangguan et al, 2013;Yao et al, 2016), some voxels may not be crossed by any signal during a tomographic process. Consequently, this will lead to an ill-posed inverse problem with incomplete input data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, numerous studies demonstrated the potential of GNSS tomography to retrieve 4-D humidity fields. Unfortunately, because the quality of the reconstructed profiles is limited by the constellation of GNSS satellites, the geographic distribution of ground-based receivers, and observation errors (Chen and Liu, 2014;Rohm et al, 2014;Shangguan et al, 2013;Yao et al, 2016), some voxels may not be crossed by any signal during a tomographic process. Consequently, this will lead to an ill-posed inverse problem with incomplete input data.…”
Section: Introductionmentioning
confidence: 99%
“…The methods for solving the abovementioned problems can be broadly divided into four categories: (1) enhancement of the precision of SWD using the "zero differences" (ZDs) technique (Alber et al, 2000;Seko et al, 2004); (2) addition of constraint conditions to tomographic models, e.g., horizontal, vertical, and boundary constraint conditions (Flores et al, 2000;Hirahara, 2000;Perler, 2011;Rohm and Bosy, 2009;Seko et al, 2000;Song et al, 2006); (3) usage of additional extra observations through RINEX met files, zenith wet delay, WVR, RS, and voxel-optimized regional water vapor tomography (Bi et al, 2006;Chen and Liu, 2014;Jiang et al, 2014;Rocken et al, 1993;Rohm et al, 2014;Yao et al, 2016); and (4) new algorithms to improve inversion quality, such as singular value decomposition (SVD), the wet refractivity Kalman filter (KF), algebraic reconstruction techniques (ARTs), and the parameterization of voxels (volumetric pixels) based on trilinear and spline functions (Bender et al, 2011;Flores et al, 2001;Gradinarsky, 2002;Gradinarsky and Jarlemark, 2004;Nilsson and Gradinarsky, 2006;Rohm et al, 2013;Shangguan et al, 2013). At present, we are focused on replacing divided voxel-based traditional methods with new, parameterized approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The first is SWD, which is the same input data used by [2] and [6] for obtaining the atmospheric wet refractivity fields. Another input parameter is SWV, which can be used to reconstruct the 3-d information of water vapour field [14,18,19]. [20] has proved that the two different classes of tomographic results can be interchangeably converted.…”
Section: Principle Of the Proposed Parameterised Approach For Tropospmentioning
confidence: 99%
“…On the one hand, the slant wet delay (SWD) was introduced to obtain the troposphere wet refractivity information (Flores et al, 2000;Skone and Hoyle, 2005;Troller et al, 2006;Rohm and Bosy, 2009;Notarpietro et al, 2011;Guo et al, 2016). On the other hand, the slant-integrated water vapor (SIWV) was applied to reconstruct the three-dimensional atmospheric water vapor field (Champollion et al, 2005;Bi et al, 2006;Xia et al, 2013;Jiang et al, 2014;Yao et al, 2016). In our project, we are trying to assimilate the three-dimensional water vapor data into a weather research and forecasting model (WRF), and this paper thus focuses on GNSS water vapor field reconstruction using SIWV data.…”
Section: Theory Of Gnss Troposphere Tomography Modelingmentioning
confidence: 99%